أزمة العلوم الإنسانية عند إدموند هوسرل - زهيرة طليبة; سمية قاسمي (جامعة الوادي - University of Eloued, 2025)
"تناولت هذه المذكرة موضوع الأزمة الإنسانية عند إدموند هوسرل، حيث تُشكّل هذه الأزمة محورا أساسيا لفهم التحولات العميقة التي شهدها الفكر الغربي في العصر الحديث، فقد لاحظ هوسرل أن الحضارة الأوروبية، رغم تقدمها العلمي والتقني، دخلت في أزمة وجودية تهدد المعنى الحقيقي للإنسان والعقل، حيث يرى أن هذه الأزمة لم تكن وليدة الحروب أو الاضطرابات السياسية فحسب، بل تعود جذورها إلى انحراف المشروع الفلسفي الغربي عن غايته الأصلية، وهي البحث عن الحقيقة وتوجيه الحياة البشرية نحو الكمال العقلي والروحي، ومع هيمنة النزعة الوضعية، أصبح العلم منغلقا على ذاته، يهتم فقط بالوقائع الموضوعية ويغفل عن الأسس المعرفية والروحية التي تمنح الإنسان معنى وجوده. لذا نسعى من خلال عملنا هذا، لتسليط الضوء على جملة من المفاهيم الأساسية التي دعا لها هوسرل من أجل إعادة بعث الفلسفة عبر تبني منهجه الفينومينولوجي، الذي يقوم على ""العودة إلى الأشياء ذاتها""، أي إلى الخبرة المعيشة والوعي بوصفه أساس كل معرفة، حيث هذا الأخير أي المنهج لا يهدف فقط إلى تجديد الفلسفة، بل إلى إنقاذ الإنسان من فقدان المعنى واستعادة الروح النقدية التي ميزت الفلسفة منذ اليونان. فهذا العمل يرتكز على تحليل رؤية هوسرل للأزمة، وتبيان كيف تشكل دعوته إلى العودة إلى الذات العاقلة محاولة لإحياء الفلسفة بوصفها مشروعا إنسانيا كونيا، كما تسعى هذه الدراسة إلى إبراز أهمية هذه الرؤية في مواجهة التحديات المعاصرة التي لا تزال تعكس جوانب من الأزمة التي وصفها هوسرل قبل قرن من الزمن." This dissertation addresses the topic of the human crisis in the philosophy of Edmund Husserl, a crisis that forms a central axis for understanding the profound transformations that modern Western thought has undergone. Husserl observed that despite the scientific and technological advancement of European civilization, it had entered an existential crisis that threatens the true meaning of both humanity and reason. Husserl maintains that this crisis is not merely the result of wars or political unrest, but rather stems from a deviation of the Western philosophical project from its original aim—namely, the pursuit of truth and the guidance of human life toward intellectual and spiritual fulfillment. With the dominance of positivist thinking, science became self-enclosed, concerned solely with objective facts while neglecting the epistemological and spiritual foundations that give human existence its meaning. Therefore, this study aims to shed light on a set of key concepts proposed by Husserl to revive philosophy through the adoption of his phenomenological method, which is based on “a return to the things themselves,” that is, to lived experience and to consciousness as the foundation of all knowledge. This method is not only intended to renew philosophy but also to rescue the human being from the loss of meaning and to restore the critical spirit that has characterized philosophy since ancient Greece. Accordingly, this work is grounded in an analysis of Husserl’s vision of the crisis, showing how his call to return to the rational self-constitutes an attempt to revive philosophy as a universal human project. This study also seeks to highlight the relevance of Husserl’s perspective in addressing contemporary challenges, which continue to reflect aspects of the crisis he described over a century ago
مذكرة ماستر قسم الفلسفة تخصص فلسفة عامة
Keywords: الإيبوخية; الفينومينولوجيا; إدموند هوسرل; أزمة العلوم الإنسانية; The crisis of the humanities; Edmund Husserl; phenomenology; epochism